2017
DOI: 10.12697/fce.2017.54.02
|View full text |Cite
|
Sign up to set email alerts
|

Lichens and allied fungi new for Latvia

Abstract: Six lichenized fungi (Calicium parvum, C. trabinellum, Carbonicola anthracophila, C. myrmecina, Peltigera extenuata, Pycnora sorophora), two lichenicolous (Clypeococcum hypocenomycis and Illosporium carneum), and two saprobic calicioid fungi (Chaenothecopsis savonica and Microcalicium arenarium) are reported as new for Latvia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The second annotated checklist of lichens listed 15 lichenicolous taxa as supplementary data (Āboliņa et al 2015). Further contribution was made by Motiejūnaitė et al (2016), with 33 lichenicolous fungi reported for the first time from Latvia, complemented by the paper of Moisejevs (2017). Since a full and up-to-date list of lichenicolous fungi for Latvia is still lacking, a comprehensive list is provided here.…”
mentioning
confidence: 99%
“…The second annotated checklist of lichens listed 15 lichenicolous taxa as supplementary data (Āboliņa et al 2015). Further contribution was made by Motiejūnaitė et al (2016), with 33 lichenicolous fungi reported for the first time from Latvia, complemented by the paper of Moisejevs (2017). Since a full and up-to-date list of lichenicolous fungi for Latvia is still lacking, a comprehensive list is provided here.…”
mentioning
confidence: 99%